Policymaking in multilevel governance: how local governments adopt sustainable development policies in Brazil - Marenco, Andre; Kern, Drisa (Frontiers in Political Science, 2025)
Brazil has a multilevel governance institutional arrangement, where environmental policies has been designed by the federal government but depend on the cooperation of the 5,570 municipalities, which have administrative autonomy for their implementation. The study goal was to investigate factors that drove municipalities to adopt legislation and regulation agencies regarding environmental management. The research (1) mapped government capacity for environmental management in municipalities; (2) verified the presence of local legislation for environmental regulation; and (3) identified determining factors for the adoption of that legislation. Four sets of factors were considered in that approach: (a) municipal state capacities, represented by environmental departments, councils, and budget; (b) policy diffusion; (c) political factors; and (d) demography. We used data from MUNIC 2020 [Survey of Basic Municipal Information], carried out by the Brazilian Institute of Geography and Statistics [IBGE], and electoral data from the Supreme Electoral Court [TSE]. Descriptive and inferential statistics—in this case, logistic regression—were used to analyze the data. Results suggested that municipalities with environmental councils are five times more likely to adopt environmental legislation, while the presence of specific secretariats increased the likelihood of legislation adoption by 29%. State capacities matter: Councils, secretariats and local civil service with higher education are the main factors that empower municipal governments to adopt environmental policies.